2019
DOI: 10.1007/s11420-019-09704-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Recurrent Dislocation after Total Hip Arthroplasty Using Advanced Imaging and Three-Dimensional Modeling Techniques: A Case Series

Abstract: Background: Surgical treatment options for addressing recurrent dislocation after total hip arthroplasty (THA) vary. Identifying impingement mechanisms in an unstable THA may be beneficial in determining appropriate treatment. Questions/Purposes: We sought to assess the effectiveness of developing pre-operative plans for treating hip instability after THA. We used advanced imaging and three-dimensional modeling techniques to perform impingement analyses in patients with unstable THA. Methods: We evaluated a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…It has been reported that THA for secondary osteoarthritis due to DDH exhibits a high dislocation rate 4,5 . Bone impingement at the AIIS after THA can be a cause of dislocation 8–10 . We proposed that pelvic morphology, including AIIS, with DDH could affect the ROM after THA.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…It has been reported that THA for secondary osteoarthritis due to DDH exhibits a high dislocation rate 4,5 . Bone impingement at the AIIS after THA can be a cause of dislocation 8–10 . We proposed that pelvic morphology, including AIIS, with DDH could affect the ROM after THA.…”
Section: Discussionmentioning
confidence: 94%
“…4,5 Bone impingement at the AIIS after THA can be a cause of dislocation. [8][9][10] We proposed that pelvic morphology, including AIIS, with DDH could affect the ROM after THA. Compared with the position of the AIIS in the pOA, the position of the AIIS in the DDH protrudes more medially and cranially from the TD, which causes an increase in ROM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning dual mobility cup, dislocation can be of two types: a loss of contact between the PE insert covering the head and the acetabular piece (classical) or an intra-prosthetic PE dislocation [ 84 ], defined as a loss of contact between the head and the PE. The latter can occur during the reduction of a classical dislocation in the early setting and lately secondary to wear [ 85 ] ( Figure 16 ).…”
Section: Complicationsmentioning
confidence: 99%